2009
DOI: 10.3758/app.71.8.1831
|View full text |Cite
|
Sign up to set email alerts
|

Dual-task interference in visual working memory: A limitation in storage capacity but not in encoding or retrieval

Abstract: The concurrent maintenance of two visual working memory (VWM) arrays can lead to profound interference. It is unclear, however, whether these costs arise from limitations in VWM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 67 publications
2
24
0
Order By: Relevance
“…When visual and tactile WM tasks have to be performed concurrently, dual-task costs could in principle arise during the encoding or maintenance of memorized sample items, or at a later stage when these items are matched to test stimuli. Current evidence for dual-task costs for WM retrieval and matching processes is mixed (Cowan & Morey, 2007;Fougnie & Marois, 2009). The fact that the modality of test stimuli is uncertain in bimodal WM tasks could affect the speed of sample-test comparisons and/or the preparation of stimulus-response mappings (cf.…”
Section: Discussionmentioning
confidence: 99%
“…When visual and tactile WM tasks have to be performed concurrently, dual-task costs could in principle arise during the encoding or maintenance of memorized sample items, or at a later stage when these items are matched to test stimuli. Current evidence for dual-task costs for WM retrieval and matching processes is mixed (Cowan & Morey, 2007;Fougnie & Marois, 2009). The fact that the modality of test stimuli is uncertain in bimodal WM tasks could affect the speed of sample-test comparisons and/or the preparation of stimulus-response mappings (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Although much recent effort has been directed at understanding verbal short-term memory (e.g., Berman, Jonides, & Lewis, 2009;Camos, Lagner, & Barrouillet, 2009;Lewandowsky, Oberauer, & Brown, 2009;Oberauer & Lange, 2008), impressive advances have also been made in the study of nonverbal stores, such as visual short-term memory (e.g., Alvarez & Cavanagh, 2008;Fougnie & Marois, 2009;Zhang & Luck, 2009). Progress in the auditory memory field, however, has been less significant.…”
mentioning
confidence: 99%
“…Wheeler and Treisman (2002) argued that attention is necessary to create and maintain binding between features over time and that this integrated representation is vulnerable to interference. Consistently, Fougnie and Marois (2009) showed that a tracking task disrupted memory for colour-shape conjunctions. By contrast, several studies indicated that binding in WM is a rather automatic process (Allen, Baddeley, & Hitch, 2006;Allen, Hitch, Mate, & Baddeley, 2012;Prabhakaran et al, 2000).…”
mentioning
confidence: 65%